2014
DOI: 10.1159/000371597
|View full text |Cite|
|
Sign up to set email alerts
|

The Prevalence of Peripheral and Central Hearing Impairment and Its Relation to Cognition in Older Adults

Abstract: Age-related hearing loss (ARHL) and dementia are two highly prevalent conditions in the adult population. Recent studies have suggested that hearing loss is independently associated with poorer cognitive functioning. The aim of this study was to evaluate the prevalence of ARHL and cognitive impairment in a large sample of subjects older than 65 years and to correlate hearing function with cognitive function. A total of 488 subjects older than 65 years (mean age 72.8 years) participating in the Great Age Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
123
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 25 publications
5
123
0
2
Order By: Relevance
“…The potential confounders that we considered were significantly associated with lower memory scores but did not cause much confounding of the relationship of hearing impairment with cognitive trajectory. These findings support studies [10,20,26] that have reported that vascular risk factors might be crucial, either as common pathological processes or as shared etiological pathways underlying both age-related hearing impairment and cognitive disorders in late life, and might be part of important prevention strategies in this field.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The potential confounders that we considered were significantly associated with lower memory scores but did not cause much confounding of the relationship of hearing impairment with cognitive trajectory. These findings support studies [10,20,26] that have reported that vascular risk factors might be crucial, either as common pathological processes or as shared etiological pathways underlying both age-related hearing impairment and cognitive disorders in late life, and might be part of important prevention strategies in this field.…”
Section: Discussionsupporting
confidence: 89%
“…Fourth, some important factors such as medication, depression, cognitive stimulation, social engagement, frailty syndrome, hypercholesterolemia, and other vascular risk factors were not examined in this study. These factors are encouraged to be incorporated in future research because they might constitute possible confounders or shared etiological pathways underlying both age-related hearing impairment and cognitive disorders in late life [10,20,26] . Fifth, in this study, selection bias because of a nonrandom loss to follow-up might have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…There is little previous literature investigating the association of HL with MCI, a prodromal stage of dementia that confers a high risk of developing dementia. A few studies have demonstrated that elevated hearing thresholds and worse performance in central auditory processing tests are evident in patients with MCI [9,21,22]. While it may not be surprising that such highly cognitively demanding tests for central auditory dysfunction (CAD) are abnormal in subjects with cognitive impairment, more convincing electrophysiological evidence of the presence of CAD in MCI is seen in increased amplitudes of auditory cortical potentials [23].…”
Section: Discussionmentioning
confidence: 99%
“…HL is consistently shown to be associated with increased risk of developing dementia in older persons of Western populations [5,6,7,8]. There has been little work investigating the relationship between HL and the risk of mild cognitive impairment (MCI), representing a transitional stage between normal healthy ageing and the development of dementia [9]. …”
Section: Introductionmentioning
confidence: 99%
“…According to recent cohort studies, the effects of hearing loss on communication and recognition are severe and are strongly associated with Alzheimer disease and Parkinson disease [6,7,8]. Central auditory processing disorder was much more closely associated with Alzheimer disease in another study [9]. However, until now the mechanism of central auditory disorder has remained unclear.…”
Section: Introductionmentioning
confidence: 99%